2021
DOI: 10.3389/fpsyt.2021.617702
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ICD-11 Personality Disorder Severity in Forensic Patients Using the Semi-structured Interview for Personality Functioning DSM-5 (STiP-5.1): Preliminary Findings

Abstract: In forensic settings, several challenges may affect reliability of assessment of personality pathology, specifically when based upon self-report. This study investigates the Semi-Structured Interview for DSM-5 Personality Functioning (STiP-5.1) to assess level of severity of personality functioning in incarcerated patients. Thirty inpatients of three forensic psychiatric facilities completed the STiP 5.1 and additionally completed self-report questionnaires assessing symptom severity, personality functioning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Most studies have been conducted with the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1; Hutsebaut et al, 2017) and the Structured Clinical Interview for the AMPD-Module I (SCID-5-AMPD-I; Bender et al, 2018). Overall good to excellent interrater reliability could be demonstrated with both, the STiP-5.1 (Hutsebaut et al, 2017(Hutsebaut et al, , 2021Weekers et al, 2021;Zettl et al, 2019) and SCID-5-AMPD-I (Buer Christensen et al, 2018;Somma et al, 2020). Test-retest reliability was also good when using the SCID-5-AMPD-I, though the coefficients for a few subdomains were questionable (Buer Christensen et al, 2018).…”
Section: Research On Lpfs-based Interviewsmentioning
confidence: 97%
“…Most studies have been conducted with the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1; Hutsebaut et al, 2017) and the Structured Clinical Interview for the AMPD-Module I (SCID-5-AMPD-I; Bender et al, 2018). Overall good to excellent interrater reliability could be demonstrated with both, the STiP-5.1 (Hutsebaut et al, 2017(Hutsebaut et al, , 2021Weekers et al, 2021;Zettl et al, 2019) and SCID-5-AMPD-I (Buer Christensen et al, 2018;Somma et al, 2020). Test-retest reliability was also good when using the SCID-5-AMPD-I, though the coefficients for a few subdomains were questionable (Buer Christensen et al, 2018).…”
Section: Research On Lpfs-based Interviewsmentioning
confidence: 97%
“…First, as the study included only self-report measures only, this could lead to method-inherent pitfalls in each sample. Empirical studies have shown that self-report scores on personality functioning should be interpreted cautiously in forensic settings ( 56 ). Secondly, it used a specific measure of BPFSC-11 which limits the results to the current measure of borderline personality.…”
Section: Discussionmentioning
confidence: 99%
“…The STiP 5.1 has shown theoretically consistent associations with other instruments assessing personality pathology, supporting construct validity (Hutsebaut et al, 2017). Replication studies have been conducted in different languages, age groups, and in a diversity of patient samples (Heissler et al, 2021; Hutsebaut et al, 2021; Weekers et al, 2020; Zettl et al, 2019). Taken together, the STiP-5.1 interview has demonstrated good psychometric properties across different samples.…”
Section: Methodsmentioning
confidence: 99%